2019
DOI: 10.29261/pakvetj/2019.093
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Indomethacin on the Norepinephrine-Induced Contraction in Vascular Smooth Muscle during Different Stages of the Estrous Cycle

Abstract: Previous studies have shown that vascular reactivity evaluated in female rat aorta to norepinephrine did not present the same response at all periods of their estrous cycle. During proestrus, the contractile response shows lower values. It was also reported that vascular reactivity had a close relationship with prostaglandins activity. In this study, we studied the response to norepinephrine in rat aorta rings treated with indomethacin. Indomethacin is a well-known inhibitor of prostaglandin synthesis. At low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The vascular reactivity in the estral cycle was studied in rat aortic rings [184]. Recently our group has reported that the indomethacin affects the norepinephrine-induced contraction in the vascular smooth muscle in different stages of the estrous cycle suggesting that cyclooxygenase produces an increase in contraction especially during proestrous [185].…”
Section: Estrous Cycle and Vascular Reactivitymentioning
confidence: 99%
“…The vascular reactivity in the estral cycle was studied in rat aortic rings [184]. Recently our group has reported that the indomethacin affects the norepinephrine-induced contraction in the vascular smooth muscle in different stages of the estrous cycle suggesting that cyclooxygenase produces an increase in contraction especially during proestrous [185].…”
Section: Estrous Cycle and Vascular Reactivitymentioning
confidence: 99%